Mechanism of Dismissal of Banyuasin Kembaran Village Apparatus in an Effort to Realize Legal Certainly (Study of Decision Number 1/G/2023/PTUN.SMG): Mekanisme Pemberhentian Perangkat Desa Banyuasin Kembaran Dalam Upaya Mewujudkan Kepastian Hukum(Studi Putusan Nomor 1/G/2023/PTUN.SMG) - Santalia, Miftah (Annual Review of Legal Studies, 2024)
The dismissal of the village apparatus of Banyuasin Kembaran Village, Loano Subdistrict, Purworejo Regency, namely the village secretary, occurred starting from the unrest of the residents and asked for the village secretary to be dismissed, so the village head has the right to sanction and dismiss the secretary. In the implementation of the dismissal that occurred to the secretary, the village head skipped the temporary dismissal mechanism. The court decision stated that the KTUN related to the dismissal of Andika Sari was cancelled. This study aims to look at the mechanism of dismissal of village officials, namely the Village Secretary of Banyuasin Kembaran and explain the ideal pattern in the implementation of dismissal of village officials based on applicable laws and regulations to realize legal certainty. The results of this study indicate that the village head dismisses the village apparatus has passed the proper procedure, namely the temporary dismissal process. Based on the ideal pattern of the mechanism for dismissing village officials, the village head should first carry out a temporary dismissal mechanism and then the village head can dismiss the village officials. in decision number 1/G/2023/PTUN.SMG states that the KTUN issued to be revoked and cancelled. Therefore, it is necessary for the village head to be careful in carrying out his duties and authority and the sub-district head who provides recommendations for dismissal to be more careful and be able to provide guidance to the village head regarding carrying out his duties in organizing the village government.